(untitled) (Journal of Hama University, 2024)
The current study aims at recognizing the level of school bullying and self-acceptance among a Sample of Sixth Grade Pupils in Hama City. It also aims at recognizing the relationship between School Bullying and Self-acceptance for the same sample. In addition, it aims at recognizing the differences between the average means in School Bullying and Self-acceptance according to gender. The sample consists of (389) in Hama City: (186) male/ (203) female. The research has created a scale for School Bullying and another scale for Self-acceptance after conducting the appropriate psychometric studies for both scales. The results of the study are: • There is (average) level of School Bullying among the sample members in the total score of the scale and its sub-dimensions. • There is (average) level of Self-acceptance among the sample members in the total score of the scale and its sub-dimensions. • There is a negative relationship between School Bullying and Self-acceptance among sample members. • There are differences in the means of sample members on the scale of school bullying according to gender for the sake of male members. • There are no differences in the means of sample members on the scale of Self-acceptance according to gender.